A Missing Citizen? Issue Based Citizenship in City‐Regional Planning. (30th October 2019) - Häkli, Jouni; Kallio, Kirsi Pauliina; Ruokolainen, Olli
Abstract: City regions are significant sites of economic development, policymaking, and everyday living. Yet in many countries they are weakly institutionalized and therefore lack established democratic practices. This article is based on a study exploring citizen participation in city‐regional planning in Finland, where traditional participatory means have largely failed to invite and involve citizens. The analysis approaches city regions relationally, as evolving processes with a changing spatial shape and scope. Through the notion of lived citizenship, including the dimensions of status, practices and acts, the article reveals how the dominant ideas of citizenship in city‐regional planning hide from view elements that are significant for citizen participation. Whereas people's rights to participation can largely be fulfilled on a territorial basis in municipalities and states through legal membership in political communities, in the context of weakly institutionalized city‐regional planning such status‐based forms of participation are typically not available. This vagueness has created an image of a missing city‐regional citizenry, which the article sets out to challenge and rework through the notion of issue‐based participation as lived citizenship.